Konsep Pendidikan Islam dalam Kitab Tasfiyah Wa Tarbiyah Karya Muhammad Nashiruddin Al-Albani - Nurazizah, Dais; Kamal, Mustopa; Darisman, Dede (Fakultas Tarbiyah, Institut Agama Islam Darussalam (IAID), Ciamis, Jawa Barat, Indonesia, 2020)
This research is motivated by the backwardness of Islamic education with others both quantitatively and qualitatively, so that Islamic education is impressed as second-class education. In fact, it is very ironic that the majority of Indonesia's population is Muslim, but in terms of education, it is always left behind with other people. Meanwhile, economic life, politics, arts and culture, knowledge and technology are considered to be world affairs which are common fields of work. The research objectives are: (1) to understand the concept of Islamic education in the tasfiyah wa tarbiyah book by Muhammad Nashiruddin al-Albani. 2) To determine the relevance of the concept of Islamic education in the tasfiyah wa tarbiyah by Muhammad Nashiruddin al-Albani with current Islamic education. The method used in this research is literature study with qualitative data analysis. This research focuses on the discussion of literature in the form of books, journals, papers and other writings that rely on data from the opinions of various experts in Islamic education. The results of this study are 1) Muhammad Nashiruddin al-Albani has 2 important things in the concept of Islamic education, namely tasfiyah and then tarbiyah. Tasfiyah is to clear Islamic teachings from human opinions and thoughts, meaning that they are not in accordance with Islamic teachings. The aim of the prioritization of tasfiyah is to invite and guide the Muslims to stick to the true and true Islamic teachings, namely the teachings of Islam exemplified by the Prophet. Educational discourse includes the concept of education, educational objectives, teaching plans, Islamic education methods, educators, facilities and infrastructure, educational environment, and evaluation.